Distributed containment control of singular heterogeneous multi-agent systems. Issue 3 (February 2020) - Zhang, Xuxi; Liu, Xianping; Feng, Zhiguang
Abstract: This paper investigates the containment control problem of singular heterogeneous multi-agent systems under directed interaction topology. Firstly, a distributed observer, in which the eigenvalue information of the leaders is not needed, is proposed to estimate the convex hull spanned by the states of the leaders. Secondly, state feedback control and reduced-order normal observer based output feedback control are presented, respectively. Finally, some numerical simulation examples are performed to demonstrate the efficiency of the proposed theoretical results.